Pembentukan Rapport di Kelas: Analisis Psikologi - Muna Erawati (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2016)
Abstract: The mastery of Arabic language is fundamental for students of Islamic Higher Education. But, generally student’s score on Arabic test did not support this expectation. Some students reported that they felt inconvenient and insecure on Arabic lesson also with the lecturer. Even though, positive relationship between lecturer and students was important for creating and also keeping student’s motivation in studying Arabic. This study aimed to analyze of rapport building between lecturer and students in classroom context. There were three questions, what kinds of strategy lecturers were applied to build and maintain rapport with students, which factors determine the building of rapport between lecturer and students, and how to describe the mechanism of rapport building between lecturer and student? Using qualitative approach, this study collected data from students and lecturers by questionnaire, observation, and interview. There were nine strategies used by lecturers to build rapport with students. The study found six factors determine the quality of lecturer and students’ rapport.Abstrak: Penguasaan Bahasa Arab penting bagi calon sarjana dari Perguruan Tinggi Keagamaan Islam. Tetapi, skor tes mereka tidak mendukung harapan ini. Sebagian mahasiswa melaporkan mereka kurang percaya diri, nyaman, dan aman saat mengikuti kuliah Bahasa Arab maupun dalam interaksi dengan dosen pengampu. Padahal perasaan aman dan nyaman tersebut bermanfaat untuk memelihara dan meningkatkan motivasi belajar mahasiswa. Riset ini bertujuan untuk menganalisis pembentukan rapport antara dosen dengan mahasiswa dalam konteks pembelajaran di kelas. Pertanyaan penelitian meliputi, apa sajakah strategi dosen yang diterapkan untuk membentuk rapport, faktor-faktor apa saja yang memengaruhi pembentukan rapport, dan bagaimana mekanisme terbentuknya rapport antara dosen dengan mahasiswa? Studi ini menggunakan pendekatan kualitatif, di mana data dikumpulkan melalui teknik kuesioner, observasi, dan interviu. Ada sembilan strategi pembentukan rapport yang ditemukan. Terdapat enam faktor yang memengaruhi pembentukan rapport dosen-mahasiswa.